THE INFLUENCE OF SELF-REGULATED LEARNING, PEER ENVIRONMENT, AND TASK AVERSIVENESS ON ACADEMIC PROCRASTINATION IN UNDERGRADUATE STUDENTS OF THE 2018 EDUCATION STUDY PROGRAM, FACULTY OF ECONOMICS, STATE UNIVERSITY OF JAKARTA: PENGARUH SELF-REGULATED LEARNING, LINGKUNGAN TEMAN SEBAYA, DAN TASK AVERSIVENESS TERHADAP PROKRASTINASI AKADEMIK PADA MAHASISWA S1 PROGRAM STUDI KEPENDIDIKAN 2018 FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - Allafannisa Maghfiroh; Ati Sumiati; Sri Zulaihati (Yayasan Education and Social Center, 2022)
Academic procrastination is a behavior of delaying work or tasks done by a person and done intentionally and repeatedly that resulted in the task not being completed optimally and causing bad habits. This research aims to find out the influence of self-regulated learning, peer environment, and task aversiveness on academic procrastination in undergraduate students of the Educational Study Program of the Faculty of Economics, Universitas Negeri Jakarta. The data collection techniques used in the study used questionnaires. The population in this study is a student of the Undergraduate Education Study Program of the Faculty of Economics, Universitas Negeri Jakarta. The sample in the study numbered 177 respondents using proportional random sampling techniques. The coefficient of determination in this study was 34.7% with the results showing that there was an influence between self-regulated learning, peer environment, and task aversiveness on academic procrastination, the rest was influenced by other variables that were not studied